(untitled) (Revista Cientifica Ingenio Magno, 2022)
This document aims to generate a methodology for the design of the drainage system, based on the Hydrology and Hydraulics component for the conception of hydraulic structures that conclude in the design for the construction and solution of several sections of third-order roads, taking as a solution, the constitution of a footprint plaque in rural areas in the municipality of Ataco – Tolima